Wood‐Derived Nanofibrillated Cellulose Hydrogel Filters for Fast and Efficient Separation of Nanoparticles. (31st July 2019) - Wang, Yushu; Wang, Jialiang; Ling, Shengjie; Liang, Haiwei; Dai, Ming; Bai, Lulu; Li, Qing; Fan, Zhuangjun; Lee, Sang‐Young; Yu, Haipeng; Liu, Shouxin; Wang, Qingwen; et al.
Abstract: Fast water permeable filters with an efficient rejection ratio are desirable for nanoparticle separation and water/air purification. Ultrathin nanoporous filters are effective because of their features, including narrow and tunable pore size distributions capable of handling a high solvent flux. However, it remains challenging to develop antifouling filters that maintain a stable flux with high rejection efficiency over long‐term filtration of nanoparticle solutions. Here, a facile and low‐cost approach is reported to fabricate biocompatible hydrogel filters with interconnected nanofiber network structures through the use of high aspect ratio, wood‐derived nanofibrillated cellulose (NFC). The super‐hydrophilia and high porosity of these materials endow the NFC hydrogel filters (NFC‐HFs) with high solvent permeance. Nanofibrous networks and interconnected nanoporous structures of NFC‐HFs promote efficient rejection and precise size‐selective separation of nanoparticles. Specifically, small and irregular nanopores of NFC‐HFs fail to match the size of relatively large nanoparticles, which ensures a relatively stable flux of the NFC‐HFs over the whole filtration process, even under continuous filtration of highly concentrated nanoparticle solutions. Abstract : Nanofibrillated cellulose hydrogel filters with interconnected porous networks are explored based on high aspect ratio wood nanocellulose building blocks. The intrinsic structure and properties of the filters make them highly permeable to the filtrated solvents accompanied with efficient nanoparticle rejection and size‐selective separation properties.